Study of flow in a non-symmetrical compound channel with rough flood plain - Bong, C.H.J (University Malaysia Sarawak, (UNIMAS), 2003)
The intention of this project is to study the flow characteristics and the discharge calculation due to the significant interaction between main channel and flood plain. However, most of the research work was done for symmetrical compound channel.